(untitled) (Journal of the College of Basic Education, 2026)
This study aims to investigate the effectiveness of using immersive learning strategies in developing musical appreciation among third-year students in the Department of Art Education. The researcher adopted the experimental method using an equivalent groups design (experimental and control). The experimental group received instruction through immersive learning environments involving multisensory experiences and virtual simulations, while the control group followed traditional teaching methods. A music appreciation scale was applied before and after the intervention. Results revealed statistically significant differences in favor of the experimental group, indicating that immersive learning effectively enhances musical appreciation, particularly in emotional engagement and analytical perception. The study recommends integrating immersive learning strategies into art and music education curricula due to their positive impact on aesthetic awareness and students’ emotional responsiveness.